Isofraxidin Inhibits Receptor Activator of Nuclear Factor-κB Ligand–Induced Osteoclastogenesis in Bone Marrow–Derived Macrophages Isolated from Sprague–Dawley Rats by Regulating NF-κB/NFATc1 and Akt/NFATc1 Signaling Pathways. (10th February 2021) - Wang, Wei; Wang, Bo
Osteoporosis is a common bone disease that is characterized by decreased bone mass and fragility fractures. Isofraxidin is a hydroxy coumarin with several biological and pharmacological activities including an anti-osteoarthritis effect. However, the role of isofraxidin in osteoporosis has not yet been investigated. In the present study, we used receptor activator of nuclear factor-κB ligand (RANKL) to induce osteoclast formation in primary bone marrow macrophages (BMMs). Our results showed that RANKL treatment significantly increased tartrate-resistant acid phosphatase (TRAP) activity, as well as the expression of osteoclastogenesis-related markers including MMP-9, c-Src, and cathepsin K at both mRNA and protein levels; however, these effects were inhibited by isofraxidin in BMMs. In addition, luciferase reporter assay demonstrated that isofraxidin treatment suppressed the RANKL-induced an increase in nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) transcriptional activity. Besides, the decreased expression level of IκBα and increased levels of p-p65, p-IκBα, and p-Akt in RANKL-induced BMMs were attenuated by isofraxidin. Moreover, NFATc1 overexpression rescued the anti-osteoclastogenic effect of isofraxidin with increased expression levels of MMP-9, c-Src, and cathepsin K. Taken together, these findings indicated that isofraxidin inhibited RANKL-induced osteoclast formation in BMMs via inhibiting the activation of NF-κB/NFATc1 and Akt/NFATc1 signaling pathways. Thus, isofraxidin might be a therapeutic agent for the treatment of osteoporosis.